Shear Strength Characteristics of Clay-Gravel Layer and Its Slope Failure Law and Mechanism - Dai, Zhangjun; Huang, Kang; Jiang, Lingfa; Li, Jian; Yu, Fei; Chen, Shanxiong (Frontiers in Earth Science, 2022)
The Anqing Formation clay-gravel layer is widely distributed in the Anqing area of the upper reaches of the Wanjiang River. It is a typical soil-rock mixture composed of gravel and clay. The poor engineering properties of the clay-gravel layer are the main factors for the failure of the slope. On the basis of regional geological survey, the clay-gravel threshold, clay mineral composition and cementation characteristics of clay-gravel layer were studied. The in-situ horizontal push-shear tests under different gravel content, water environment and overlying load were designed and carried out, and its shear failure mode and strength were analyzed. The study found that the shear zone was in the shape of a broken line and was controlled by the particle size and distribution of the gravel. The shear strength of the clay-gravel layer is relatively high in the natural state due to the structure of the gravel and the friction and cementation force between the clay and the gravel. Water had the greatest influence on the shear strength of the clay-gravel layer, and the overlying load affected its shear strength within a certain range. The indoor rainfall erosion model test of the clay-gravel slope was carried out, and the failure and instability modes and mechanisms of the slope with different gravel contents were studied. When the gravel content was 30%, the failure of the slope surface was the development of gullies. The erosion damage process was similar to the soil slope. When the gravel content was 50%, affected by the distribution of gravel, the slope failure was manifested as the development of erosion pits, followed by local slumps, and finally the overall sliding in layers. When the gravel content was 70%, the clay particles on the slope were quickly washed away by the water flow, and the gravel skeleton of the slope formed a temporary relatively stable structure. After being disturbed, the gravel layer collapsed as a whole.